Urban heat island phenomenon in a desert, coastal city: The impact of urbanization - J.R. Rajeswari (22046561) (2024)
The state of Qatar has been experiencing rapid urbanization with around 85% of its population residing in Doha. The country faces notable challenges related to the Urban Heat Island (UHI) effect, which is exacerbated by its hot and humid desert climate. This study focuses on analyzing the UHI phenomenon in Doha, utilizing observed meteorological data and the Weather Research and Forecasting model (WRF v4.5). Two land use and land cover (LULC) datasets from 2001 and 2018 are employed, with simulations conducted using different urban canopy models. The 2018 LULC data includes 100 m resolution information that categorizes urban areas into 11 local climate zones. Results indicate significant UHI intensity during both winter and summer periods (up to 6.5 °C), with notable differences observed between daytime and nighttime temperatures. In agreement with observations, the model predicts not only a strong UHI effect during nighttime, but also a significant Urban Cool Island effect in Doha (up to −5.8 °C during daytime in summer). The impact of various urban parameterization schemes on simulation accuracy is highlighted. The building energy model demonstrates superior performance in predicting temperature and relative humidity during the summer period. The spatial distribution of heat index illustrates the intensified warming in the city. Other Information Published in: Urban Climate License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.uclim.2024.102016